A Review Of Methods To Protect The Environment In Dam Projects - Hossein Mohajeri; Seyyed Mohammad Amin Najibi; Mahdi Shahraki (مهندسی و مدیریت ساخت, 2016)
Studies and studies have shown that the construction of a dam and reservoir in the reservoir will have significant physico-chemical and ecological effects on the system. In fact, building a dam can affect the environment both directly and indirectly and in a wide range. In this study, the environmental effects of dam construction have been investigated. Then, considering environmental impacts, environmental protection methods are discussed in dam construction projects. The present study has shown that investing in new ways of protecting the environment is inevitable in order to reduce these adverse effects. On the other hand, the concept of sustainable development in the future planning of dams should be considered. All environmental impacts of a dam in the catchment area of ​​the watershed should be estimated in a comprehensive environmental, social and economic study. Finally, considering the environmental effects and protective methods, the importance of interdisciplinary perspective is discussed.